عمل المرأة خارج البيت دراسة مقارنة بين الشريعة الإسلامية والقانون الفلسطيني واتفاقية سيداو - Ahmed R. M Raddad
The research problem lies in the spread of the work of women in society under international laws and conventions that call for the work of women without any restrictions. These calls has emerged from the widespread of women organizations and civil societies that are seeking to enforce (CEDAW) convention which is conflicted in many of its articles with Islamic “Shariah” Law, the Palestinian Law and the customs and norms of the Palestinian community. This study aimed to explain the real position of women in the Islamic religion and the Islamic “Shariah” as well as women’s right in the Palestinian Law. The study also aimed at explaining the attitudes of the Islamic Law, the Palestinian Law and (CEDAW) convention towards the work of women. In addition, the study aimed to identify the rules of Islamic Shariah” that regulated the work of women outside homes and the extent of its consistency with the Palestinian Law and CEDAW. The researcher used the inductive methodology through studying the views of scholars related to the subject of women's work. In addition to that, the researcher applied the analytical comparative approach where comparison between (CEDAW) convention and Islamic“Shariah” and the Palestinian Law were conducted, and where the points of agreement and disagreement between them were studied. The study found that women’s work is one of the main rights that were emphasized by Islamic“Shariah” and ordinances. It emphasized the importance of women’s commitment to Islamic“Shariah” at the workplace.